Impact of Sustainable Supply Chain Management Practices on Egyptian Companies’ Performance - Mamdouh Mahmoud Hamdy, Ola; Kadry Elsayed, Khaled; Elahmady, Bassam (European Journal of Sustainable Development, 2018)
The adoption of the Sustainable Supply Chain Management practices by companies in the private sector of Egypt aids to achieve its sustainable development strategy: Egypt Vision 2030, which aligns with the seventeen SDGs launched by the United Nations in 2015. There is a trade-off between sustainable development and economy. The trade-off lies between the benefits that result from adopting environmental, social or resilient practices by companies, versus the costs incurred due to conducting these practices. The research problem is that companies in Egypt regard sustainable practices as a burden to their profitability and continuity. In addition to that, companies do not link application of Sustainable Supply Chain Management (SSCM) practices with their performance. The hypothesis tests whether or not there is a significant impact for applying Sustainable Supply Chain Management (SSCM) practices on the company’s performance measures. The research studies the impact of this application on the economic, environmental and operational performance of these companies. A survey tool is designed to collect the data from managers and employees in the supply chain departments of companies that are listed on the Egyptian corporate responsibility index (S&P/ EGX ESG Index) and the sample is expanded by including their market peer companies in the EGX100. Keywords: Egypt, Sustainable Supply Chain Management, Green Supply Chain Management, Social Sustainability, Resilient Supply Chain, Performance